2016
DOI: 10.1111/hepr.12644
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymer‐dependent 3D culture accelerates the differentiation of HepaRG cells into mature hepatocytes

Abstract: Aim:The hepatoma-derived cell line HepaRG is regarded as an in vitro model of drug metabolism because fully differentiated HepaRG cells demonstrate functional metabolic responses comparable to those of primary human hepatocytes. Recently, it was demonstrated that the 3D culture of HepaRG cells enhanced their metabolic functions and toxicological responses. We approached the mechanisms underlying these enhancement effects.Methods: We compared 2D-cultured HepaRG cells with 3D-cultured HepaRG spheroids in the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 32 publications
5
51
0
1
Order By: Relevance
“…HepaRG is a bipotent human liver progenitor cell line that is capable of differentiating into hepatocyte‐like cells (HLCs) (Higuchi et al, ) and biliary epithelial‐like cells (BECs) (Cerec et al, ; Leclerc et al, ; Leite et al, ). HepaRG‐derived hepatocyte‐like cells (HepaRG‐HLCs) have been shown to exhibit similar metabolic functions as primary human hepatocytes (Hoekstra et al, ; Leite et al, ), and have been extensively explored as an alternative human hepatocyte cell source in drug metabolism and toxicity testing (Leite et al, ; Wang et al, ) as well as disease modeling (Marion et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HepaRG is a bipotent human liver progenitor cell line that is capable of differentiating into hepatocyte‐like cells (HLCs) (Higuchi et al, ) and biliary epithelial‐like cells (BECs) (Cerec et al, ; Leclerc et al, ; Leite et al, ). HepaRG‐derived hepatocyte‐like cells (HepaRG‐HLCs) have been shown to exhibit similar metabolic functions as primary human hepatocytes (Hoekstra et al, ; Leite et al, ), and have been extensively explored as an alternative human hepatocyte cell source in drug metabolism and toxicity testing (Leite et al, ; Wang et al, ) as well as disease modeling (Marion et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…While human stem cell‐derived hepatocytes differentiated on conventional 2D cultures are being extensively investigated for applications in disease modeling as well as drug metabolism and toxicity testing (Leite et al, ; Wang et al, ), their differentiation and maturation in a microfluidic 3D hepatocyte culture platform have not yet been demonstrated. Similar to primary hepatocytes, stem cell‐derived hepatocyte‐like cells (HLCs) cultured in a 3D configuration as spheroids in micro‐wells and scaffolds showed a functionally more mature phenotype with higher liver‐specific functions (Gieseck et al, ; Higuchi et al, ; Tasnim et al, ; Wang et al, ). Therefore, we postulate that a liver‐sinusoid‐inspired microfluidic 3D microenvironment can enhance the differentiation and maturation of human liver progenitor cells into HLCs.…”
Section: Introductionmentioning
confidence: 99%
“…The current study showed that culturing MSCs in heparinized 3D scaffold at the presence of hepatogenic media led to an increase in the frequency of albumin-and cytokeratin 19-positive cells and also a rise in the intensity of the reaction for all tested liverspecific markers. Heparinized collagen sponges have been detected to improve hepatocyte functions (20). Indocyanine green clearance test showed MSC-derived hepatocyte functions also are promoted in heparin/collagen sponges, as well.…”
Section: Discussionmentioning
confidence: 98%
“…Also, an improvement in hepatocyte function and bio-mimicking of toxicity response has been reported through 3D culture (19). The 3D culture condition can lead to the acceleration of hepatocyte maturation (20). GAGcontaining collagen scaffolds have been previously used in tissue engineering context for both in vivo and in vitro studies to improve cellular attachment, metabolism, viability, as well as cell-matrix interactions (18).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transplantation of three-dimensional-cultured hepatoma-derived cell line HepaRG cells has been reported to yield hepatocyte-like colonies in in vivo mouse bodies, like primary human hepatocytes, suggesting a possible human cell source for steady generation of humanized liver TK-NOG mice. 54,55 Humanized mice reconstituted with human immune systems are also essential to study human immune reactions in vivo and are expected to be useful for studying human allergies. A novel transgenic NOG strain bearing human interleukin-3 and granulocyte macrophage colony-stimulating factor genes has been developed.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%